Aṣlak eh ? De juif en Égypte à Juif d’Égypte - Michèle Baussant (Diasporas: Circulations, Migrations, Histoire)
This study examines Jews expelled from Egypt and currently settled in France. Its main focus is to understand the different links with Egypt and an Egyptian Jewish identity, taking into account the diversity of experiences and ties with the home country and their connection to memory. Three main themes are addressed: the question of heritage linked to that of memory, the Arabic language, and leaving Egypt. These issues are central to comprehending how the transition in status occurred from being ‘Egyptian Jews’ or ‘Jews in Egypt’ to that of ‘Jews from Egypt.’